Buku Cerita Bergambar Ungkapan Larangan Daerah Minangkabau Untuk Anak-Anak Koto Berapak Pesisir Selatan - Yunal Mahendri; Hendra Afriwan (Lembaga Pengembangan Kinerja Dosen, 2023)
Prohibited expressions are part of people's beliefs, referred to as people's beliefs because there is an association relationship in them. The culture of this prohibition expression has begun to disappear along with the changes or developments of the times. The purpose of making this picture story book is to preserve the Minangkabau culture of forbidden expressions and to explain the good intentions behind the prohibition phrases for young people today, especially the children of Koto Bersisir Selatan. With the media of interesting picture story books, it is hoped that this media will facilitate adolescents' understanding of the information conveyed, as well as increase interest in reading. The design of this work uses the glassbox design method with the design stages of preparation, incubation, lumination, and verification. 5W+1H data analysis method (What, When, Where, Who, Why, and How. In addition to designing picture books as the main media, this design has supporting media, namely posters, digital posters, x-banners, t-shirts, bookmarks , upload social media Instagram, Facebook, Twitter, and E-book.